Unambiguous Sine-phased BOC(kn,n) Signal Acquisition Based on Combined Correlation Functions - Deng Zhongliang; Xi Yue; Yin Lu (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2015)
Galileo and GPS have been developing their new signals in recent years. Multiplexed Binary Offset Carrier (MBOC) is the final implementation of Galileo E1 and GPS L1C, which is the multiplexing of BOC(1,1) and BOC(6,1). Therefore, it is helpful to satisfy the demand that the new signals must be compatible with GPS BPSK signal. BOC(kn,n) modulation will provide better track performance and higher positioning accuracy. However, the main drawback of the BOC modulated signal is that its autocorrelation has multiple side peaks around the main peak. This paper will focus on a family of signals: sine-phased BOC(kn,n). We are trying to explore a new method to cancel the side peaks of BOC(kn,n) autocorrelation, making use of two kinds of correlation functions. One is the correlation of the incoming signal and the sine-phased BOC(kn,n) modulated spreading code(PRN code multiplied by subcarrier), and the other is the correlation of the incoming signal and the PRN code only. Two kinds of correlation function are separated into several sub-correlations. Sub-correlations have less side peaks which are in different code delays. Corresponding parts of two sub-correlations will be combined to cancel the side peaks separately, and finally the new function without side peaks will be acquired after several correlations added together. Simulation results will be given. It is shown that the proposed method is contributed to the side peaks cancellation for unambiguous sine-phased BOC (kn, n) signal acquisition.